Unreliable Protection: An Experimental Study of Experts' In Bello Proportionality Decisions. (21st September 2020) - Statman, Daniel; Sulitzeanu-Kenan, Raanan; Mandel, Micha; Skerker, Michael; De Wijze, Stephen
Abstract: The proportionality principle is an international humanitarian law requirement intended to constrain the use of military force in order to protect civilians in armed conflicts. This research experimentally assesses the reliability of its application by legal and moral experts (in 11 countries), by military officers (in two countries) and by laypeople. Reliability was evaluated according to three criteria: inter-expert convergence; sensitivity to relevant factors; and robustness – relative (lack of) susceptibility to biases. Unlike laypeople, experts and military officers performed well on the sensitivity criterion and manifested an appropriate understanding of the principle at the abstract level. However, both groups of experts failed to reach reasonable judgment convergence. These findings cast doubt on the reliability of the protection provided to civilians during warfare, even when warring parties attempt to abide by the proportionality principle.